Functional topography of the corpus callosum as revealed by fMRI and behavioural studies of control subjects and patients with callosal resection. (3rd May 2023) - Fabri, Mara; Polonara, Gabriele
Abstract: The concept of a topographical map of the corpus callosum (CC), the main interhemispheric commissure, has emerged from human lesion studies and from anatomical tracing investigations in other mammals. Over the last few years, a rising number of researchers have been reporting functional magnetic resonance imaging (fMRI) activation in also the CC. This short review summarizes the functional and behavioral studies performed in groups of healthy subjects and in patients undergone to partial or total callosal resection, and it is focused on the work conducted by the authors. Functional data have been collected by diffusion tensor imaging and tractography (DTI and DTT) and functional magnetic resonance imaging (fMRI), both techniques allowing to expand and refine our knowledge of the commissure. Neuropsychological test were also administered, and simple behavioral task, as imitation perspective and mental rotation ability, were analyzed. These researches added new insight on the topographic organization of the human CC. By combining DTT and fMRI it was possible to observe that the callosal crossing points of interhemispheric fibers connecting homologous primary sensory cortices, correspond to the CC sites where the fMRI activation elicited by peripheral stimulation was detected. In addition, CC activation during imitation and mental rotation performance was also reported. These studies demonstrated the presence of specific callosal fiber tracts that cross the commissure in the genu, body, and splenium, at sites showing fMRI activation, consistently with cortical activated areas. Altogether, these findings lend further support to the notion that the CC displays a functional topographic organization, also related to specific behavior. Graphical abstract: Image 1 Highlights: Lesion, behavior, and DTI studies show that human CC is topographically organized. A similar organization is evident in mammals CC after tracing investigations. Sensory stimuli and simple motor or behavior tasks evoke activation in human CC. The CC activations display a functional topographical organization. The CC topographical organization is consistent with previous reports.